2016
DOI: 10.4103/0974-777x.182129
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of serum th1/th2 cytokine levels in patients with acute mumps infection

Abstract: Background:The mumps virus is frequently the causative agent of parotitis. There has been no study on serum cytokine levels of acute mumps parotitis except for a few which document cytokine levels in cerebrospinal fluid of mumps meningitis. It is with this notion, our study aimed to find Th1/Th2 cytokine levels from patients with acute mumps parotitis.Materials and Methods:Concentrations of mumps-specific IgM, mumps, measles, rubella-specific IgG antibody, and Th1/Th2 cytokines, namely interferon-γ (IFN-γ), in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…It has been reported that severe mumps cases are characterized by elevated levels of IL-6 and IFN-γ in plasma [6], while another study also noted that IL-2 and IFN-γ were increased in serum of patients with acute mumps infection, thus indicating an important role for Th1 cells in this disease [7]. Likewise, inflammatory processes occurring in meninges during mumps meningitis seem to be similar, as IFN-γ, IL-2, and IL-6 levels are significantly elevated in the CSF of affected patients, while TNF-α in the CSF does not show an elevated level [8], though an increased level of that cytokine is a feature of patients with tuberculous meningitis [9].…”
Section: Discussionmentioning
confidence: 92%
“…It has been reported that severe mumps cases are characterized by elevated levels of IL-6 and IFN-γ in plasma [6], while another study also noted that IL-2 and IFN-γ were increased in serum of patients with acute mumps infection, thus indicating an important role for Th1 cells in this disease [7]. Likewise, inflammatory processes occurring in meninges during mumps meningitis seem to be similar, as IFN-γ, IL-2, and IL-6 levels are significantly elevated in the CSF of affected patients, while TNF-α in the CSF does not show an elevated level [8], though an increased level of that cytokine is a feature of patients with tuberculous meningitis [9].…”
Section: Discussionmentioning
confidence: 92%